1970
DOI: 10.4314/ejhs.v29i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogens in Under-Five Children with Diarrhea in Health Facilities of Debre Berhan Town, North Shoa, Ethiopia

Abstract: BACKGROUND: Diarrheal disease is a major cause of mortality and morbidity for under-five children in Ethiopia. The purpose of this study was to investigate the behavioral and socioeconomic risk factors, etiology, and drug susceptibility of bacteria isolated from under-five children with acute diarrhea who were treated at Debre Berhan Referral Hospital or Health Center in Ethiopia.METHODS: A health facility based cross-sectional study design was used to investigate enteropathogens from 163 under-five children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Pathogens such rotavirus, adenovirus, Shigella and norovirus have been documented as the leading causes of diarrhea in the same study areas ( Hugho et al, 2023 ). Our findings are in line with similar findings in other studies in Tanzania ( Moyo et al, 2011 ) and Ethiopia and Iraq ( Harb et al, 2017 ; Zelelie et al, 2019 ), and the reported prevalence of Salmonella was low compared to studies conducted in other countries ( Azemi et al, 2013 ; Langendorf et al, 2015 ). This study identified six distinct STs from isolates obtained in diarrheal samples.…”
Section: Discussionsupporting
confidence: 92%
“…Pathogens such rotavirus, adenovirus, Shigella and norovirus have been documented as the leading causes of diarrhea in the same study areas ( Hugho et al, 2023 ). Our findings are in line with similar findings in other studies in Tanzania ( Moyo et al, 2011 ) and Ethiopia and Iraq ( Harb et al, 2017 ; Zelelie et al, 2019 ), and the reported prevalence of Salmonella was low compared to studies conducted in other countries ( Azemi et al, 2013 ; Langendorf et al, 2015 ). This study identified six distinct STs from isolates obtained in diarrheal samples.…”
Section: Discussionsupporting
confidence: 92%
“…According to the WHO, Africa and South-East Asia account for 78% of all diarrheal infant fatalities in poor countries. Poor environmental circumstances, socioeconomic level and behavioral characteristics are all substantially connected with the probability of transmission of diarrhea 1 . According to the onset and extent, diarrhea is classified into acute (<7 days), prolonged (7-14 days) and chronic (>14 days).…”
Section: Introductionmentioning
confidence: 99%
“…These are disseminated from the affected people through the oro-fecal route 5 . Parasitic infections associated with diarrhea include Ascaris lumbricoides; Giardia lamblia, Hymnolepis nana, Entamoeba histolytica, Cryptosporidium, Blastocystis hominis, Trichuris trichiura, and Cyclospora cayetanensis 1,6 . Rotavirus is the most prevalent viral cause of gastroenteritis associated with severe diarrhea, which kills 400,000 children per annum throughout the globe [7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…However, majority of the studies conducted on diarrheagenic bacteria like; DEC, Salmonella, Shigella, and Campylobacter spp. in Ethiopia have reported only the pathogen prevalence in; diarrheic UFC 11,[19][20][21][22][23] or other age groups 24,25 and in asymptomatic food handlers in catering establishments and street food vendors 16,[26][27][28][29][30][31] as a separate entities. They do not focused on tracking of direct human contacts as source attributions for diarrhea diseases.…”
Section: Introductionmentioning
confidence: 99%
“…4 , 5 A study conducted in Hawassa and Debre Berhan indicated bacterial pathogens particularly Campylobacter , Shigella , and Salmonella spp. 10 and E. coli 11 are the main cause of childhood diarrhea accounting about 22.2% among the overall causative pathogens identified. The prevalence may be higher in eastern Ethiopia including Harar town and Kersa district where people have limited understanding of zoonotic disease and hand washings 12 , 13 and practicing open defecation.…”
Section: Introductionmentioning
confidence: 99%